Effectiveness and Safety of Novel Nutraceutical Formulation Added to Ezetimibe in Statin-Intolerant Hypercholesterolemic Subjects with Moderate-to-High Cardiovascular Risk - Mazza, Alberto; Nicoletti, Mariaceleste; Lenti, Salvatore; Torin, Gioia; Rigatelli, Gianluca; Pellizzato, Marzia; Fratter, Andrea (Journal of medicinal food, 2021)
The effectiveness of statins in the primary and secondary prevention of cardiovascular (CV) diseases has been widely proven. However, the onset of adverse events associated with their use prevents to achieve the therapeutic targets recommended by the guidelines (GL) for the management of dyslipidemia. In the event of statin intolerance, the GL recommend to use bile acid sequestrants, fibrates, and ezetimibe in monotherapy, but their benefits in improving lipid pattern are quite modest. This study aims at evaluating the effectiveness and safety of a nutraceutical compound (NC) associated with ezetimibe (EZE) on the lipid profile in statin-intolerant patients with moderate-to-high CV risk. Ninety-six statin-intolerant hypertensive and hypercholesterolemic subjects treated pharmacologically with EZE 10 mg daily were randomized in open label ( = 48) to take for 3 months a NC containing Monacolin-K (MK), Berberine Hydrochloride (BC), t-Resveratrol (RES), Quercetin (QUER), and Chromium (CH) in the form of a gastro-resistant tablet that improves enteric bioaccessibility and bioavailability of these substances. The control group ( = 48) took only EZE in monotherapy at the same dosage; both groups followed a standardized lipid-lowering diet. The total serum cholesterol (TC), low density lipoprotein cholesterol (LDLC), high density lipoprotein cholesterol (HDLC), triglycerides (TG), aspartate aminotransferase (AST), alanine aminotransferase (ALT), and creatinine phosphokinase (CPK) levels were compared at the follow-up in both groups using Student's -test. TC and LDL levels reduced in both groups, but were lower in the group treated with EZE + NC (-25.9% vs. -15%, < .05 and -38.7% vs. -21.0%, < .05, respectively). No changes were observed in either group regarding a decrease in TG (-9.4% vs. -11.7%, NS) and an increase in HDLC (+4.2% vs. +1.1%, NS). The AST, ALT, and CPK levels increased in the group treated with the EZE + NC compared to the control group, but were still within the acceptable range. There was no difference concerning the lipid-lowering treatment between gender, and no patient withdrew from the study. In the short term, the EZE + NC combination therapy is well tolerated and effective in improving TC and LDLC levels in statin-intolerant patients with moderate-to-high CV risk.